2017
DOI: 10.1093/sleep/zsx202
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Sleep Duration: Bidirectional Associations Among Chronotype, Social Jetlag, and Drinking Behaviors in a Longitudinal Sample of US High School Students

Abstract: Health Behavior in School-Aged Children: NEXT Longitudinal Study 2009-2013, https://clinicaltrials.gov/ct2/show/NCT01031160?term=Simons-Morton&rank=3, NCT01031160.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 71 publications
4
45
2
Order By: Relevance
“…We found a mean social jetlag of 2.80 hours in this large sample of adolescents, with no between-sex differences (2.80 in females and 2.81 in males). Population-level studies of social jetlag in adolescents demonstrate average social jetlag levels around 2.50 (Haynie et al, 2018;Vollmer et al, 2017), similar to the current sample. These levels of social jetlag in adolescents contrast sharply with population-level studies in adults, which find the majority of adults having social jetlag ≤ 1 hours (Islam et al, 2018;Koopman et al, 2017;Parsons et al, 2015), translating to about 250% greater social jetlag in adolescents versus adults.…”
Section: Discussionsupporting
confidence: 81%
“…We found a mean social jetlag of 2.80 hours in this large sample of adolescents, with no between-sex differences (2.80 in females and 2.81 in males). Population-level studies of social jetlag in adolescents demonstrate average social jetlag levels around 2.50 (Haynie et al, 2018;Vollmer et al, 2017), similar to the current sample. These levels of social jetlag in adolescents contrast sharply with population-level studies in adults, which find the majority of adults having social jetlag ≤ 1 hours (Islam et al, 2018;Koopman et al, 2017;Parsons et al, 2015), translating to about 250% greater social jetlag in adolescents versus adults.…”
Section: Discussionsupporting
confidence: 81%
“…The mechanism underlying this association is still unclear, but it is proposed that both alcohol and caffeine intakes can delay the onset on nocturnal melatonin release, thus suppressing sleepiness [83,91]. Interestingly, some studies revealed how the consumption of alcohol and caffeine can increase the odds of later chronotype [90,92]. It was postulated that evening chronotypes have more chances to engage with 'evening habits' (drinking) due to a delay in sleep time compared to morning chronotypes, who sleep earlier [93].…”
Section: Macro and Micro Nutrients And Food Groupmentioning
confidence: 99%
“…Recent research also highlights the high level of variability in nightly sleep duration during adolescence (Cysarz et al, 2018, Urbanek et al, 2018). Nightly sleep variability is associated with multiple health risks in adolescents; including, increased risk of obesity and poor diet (He et al, 2015; Malone et al, 2016), chronic inflammation (Park et al, 2016), substance use (Haynie et al, 2017, Nguyen-Louie et al, 2018), behavioral disorders (Zhang et al 2017), and mental health problems/negative mood (Bei et al, 2017, Fuligni and Hardway, 2006, Zhang et al, 2017). Thus, in addition to the health risks posed by insufficient mean hours of sleep (Wahlstrom, Berger, & Widome, 2017), variability in sleep may produce health disadvantages among adolescents who are unable to establish regular sleep schedules.…”
Section: Introductionmentioning
confidence: 99%